2012
DOI: 10.1029/2012wr012067
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of flow direction methods against field observations of overland flow dispersion

Abstract: The D8, D8-LTD, D∞-LTD, D∞, MD∞, and MD8 flow direction methods are evaluated against field observations of overland flow dispersion obtained from novel experimental methods. Thin flows of cold water were released at selected points on a warmer slope and individual overland flow patterns originating from each of these points were observed using a terrestrial laser scanner and a thermal imaging camera. Land microtopography was determined by using laser returns from the dry land surface, whereas overland flow pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…The analysis shown by Orlandini et al . [] reveals that the dispersion produced by multiple flow direction methods strongly depends on grid cell size, and suggests therefore that caution must indeed be exercised in the application of multiple flow direction methods for the description of overland flow dispersion. Even under a broad perspective, slope lines remain essential topographic attributes for the description of overland flows because (1) they provide the surface flow paths along which gravity‐driven, nondispersive flows of water and sediments extend, and (2) they provide the skeleton around which dispersive overland flow patterns are likely to develop.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis shown by Orlandini et al . [] reveals that the dispersion produced by multiple flow direction methods strongly depends on grid cell size, and suggests therefore that caution must indeed be exercised in the application of multiple flow direction methods for the description of overland flow dispersion. Even under a broad perspective, slope lines remain essential topographic attributes for the description of overland flows because (1) they provide the surface flow paths along which gravity‐driven, nondispersive flows of water and sediments extend, and (2) they provide the skeleton around which dispersive overland flow patterns are likely to develop.…”
Section: Introductionmentioning
confidence: 99%
“…McMaster (2002) found that both algorithms can perform equally well when deriving channel networks for steep terrain. Orlandini et al (2012) field tested the performance of six different eight and infinite directional routing algorithms, finding that network shapes were affected by grid cell size and that the planar dispersion represented in multi-direction flow algorithms decreased quickly as flow proceeded downslope. Flow direction information can be used to estimate the area of land contributing flow to a given cell as the sum of the areas of all upslope contributing cells.…”
Section: Introductionmentioning
confidence: 99%
“…The other approach is to set a single flow direction for each grid cell (nondispersive methods) considering other elements in addition to local slopes; such that on average, the flow path is unbiased (e.g., Fairfield & Leymarie, 1991;Lea, 1992;Orlandini et al, 2003;Paik, 2008;Zhou, Pilesjö, & Chen, 2011). No perfect method exists for surface flow routing; dispersive and nondispersive methods each have merits depending on the application they are used for (Orlandini et al, 2012).…”
Section: Introductionmentioning
confidence: 99%